Membangun Solidaritas Kemanusiaan: Kritik Nabi Amos Terhadap Praktik Pelanggaran Hak Asasi Manusia - Gernaida K.R. Pakpahan (Manna Rafflesia, 2021)
This research aims to explore the implementation of human rights in the 8th century BC. The prophet Amos's criticism was aimed at the failure of nations to build human solidarity which was shown in various human rights violations. The approach method used is a form criticism approach, a synchronic and diachronic approach that seeks to examine the historical context of the book of Amos. The results obtained from the research show that violations of human rights during the Amos era include: deprivation of one's right to life and property, trafficking and human slavery, loss of fraternal solidarity, anger, and revenge, intimidation, terror and fear, the humiliation of human beings, refusal. rule of law. Israel's crimes against humanity are driven by a materialistic spirit so that it carries out the sale of the righteous, the poor, the weak, the exploitation of women, fines, and debts. Building humanitarianism through law enforcement so that truth and justice are created in society.